The smashing machine [videorecording (Blu-Ray)] - Safdie, Benny; Johnson, Dwayne, 1972-; Blunt, Emily; Bader, Ryan; Rutten, Bas, 1965-; Usyk, Oleksandr (A24, 2026)
MMA fighter Mark Kerr reaches the peak of his career but faces personal hardships along the way.